Specific bronchial hyperreactivity and hypersensitivity in patients with allergic asthma - Aćimović, Slobodan; Lončarević, Olivera LJ; Vuković, Jelena; Stojsavljević, Marko; Rančić, Nemanja (Vojnosanitetski pregled, 2017)
Background/Aim. Bronchial asthma is a disease that is characterized by the variability of the clinical picture, physical and functional status and the existence of bronchial hypersensitivity and hyperreactivity with varying degrees. Bronchial responsiveness and sensitivity are tested in patients with clinically suspected existence of asthma and normal spirometry test. The aim of the study was to analyze the patients with atopic asthma and study test results of skin sensitization to inhaled allergens, nonspecific bronchial hyperreactivity and specific hyperreactivity estimated by bronchial provocation tests with inhalant allergens. Methods. The prospective study at the Pulmonology Clinic of the Military Medical Academy in Belgrade Serbia, during 2014, included 70 male subjects aged 18–30 years, who had perennial asthma symptoms. All subjects were nonsmokers, with normal spirometry findings, with normal radiological chest findings and with no symptoms of respiratory infection over the past two months. All respondents were tested with skin prick tests with inhalant allergens and nonspecific bronchial provocation test with histamine. On the basis of histamine test, subjects were divided into two groups: the group I, in which there was a slight degree of hypersensitivity [provocation concentration of histamine causing a 20% fall in forced expiratory volume – PC20 = 6.09 ± 1.1 mg/mL], and the group II with negative histamine test (PC20 = 14.58 ± 6.34 mg/mL). Specific bronchial provocation test was performed in all patients, and the selection of the allergens was carried out based on the results of testing of skin hypersensitivity. Results. Results of skin sensitization show the highest incidence of mites Dermatophagoides pterronissinus (83.3% group I and 85.0% group II) followed by grass pollen (53.3% group I and 52.0% group II), and house dust (33.3% group I and 50.0% group II). There were no statistically significant differences in allergens between groups (p > 0.05). In both groups, spirometry findings were within normal values [forced vital capacity – FVC and forced expiratory volume 1 – FEV1 > 80% predictive value], but statistically significant difference was found in FEV1 between groups (p < 0.05). Specific bronchial provocation tests with solutions of inhaled allergens in both groups caused a significant decline in FEV1 (≥ 20%) in all patients individually. No statistically significant differences were found neither between groups, nor between individual allergens (average decline in FEV1: Group I 32.9 ± 2.4% and group II 31.5 ± 2.2%). Conclusion. There is no relationship between the degree of specific and non-specific bronchial hyperreactivity in patients with allergic asthma.